Buddhist Method Administration of Agricultural Community Learning Center - Sisabai, Suphattharachai (Journal of Multidisciplinary in Humanities and Social Sciences, 2020)
Agricultural Community Learning Center. It is one of the Approaches to Agricultural Development According to the National Development Plan No. 12. Group of People in the Community. Center of Information, Message, Agricultural Knowledge for the People in the Community. This will lead to the opportunity to Learn, Relay, Exchange Experiences, Inheritance Wisdom, Culture, Values , and Identity of the Community. It is an Agricultural Community Resource. Provides a Community of Learning and Focus on the Development of Self-Reliant Farming. It is the Center of Public Learning operated by the People for the People. The Operation of the Agricultural Community Learning Center Requires Good Administration. Using the theory of "POLE" including Planning, Organizing, Leading and Controlling by Integration with the Principles of Buddhism is the Basis for Success. The Fairness that is used in the Management of Success includes Aspiration, Effort, Thoughtfulness, Investigation. It is called the "Buddhist Method Administration of Agricultural Community Learning Center" This will Lead to Effective and Productive Results.